Endovascular Materials and Their Behavior in Peripheral Vascular Surgery - Mazzaccaro, Daniela; Giannetta, Matteo; Righini, Paolo; Modafferi, Alfredo; Malacrida, Giovanni; Nano, Giovanni (Frontiers in Surgery, 2022)
Endovascular techniques have progressively become the first option for the treatment of stenosis and occlusions of both aorto-iliac and femoro-popliteal district. The development of new technologies and new materials have broadened the applicability of the endovascular techniques, allowing the treatment of each lesion with the most suitable material. The knowledge of the behavior of the endovascular materials when treating peripheral arterial disease (PAD) is therefore crucial for optimization of the results. We aimed to review the most important technical features of the actually available endovascular materials for treating PAD.